Exogenous enzyme increased feed intake but not growth and feed efficiency of sheep fed edamame wastes - Marzuki, A; Syahniar, T M; Andriani, M; Nusantoro, S; Kustiawan, E (Food and Agricultural Sciences : Polije Proceedings Series, 2020)
Feed management strategies, for example using cheap agricultural by product to reduce feed cost, are commonly used in improvement of livestock farming. This research aimed to access efficacy of commercial exogenous enzyme (consisting of mixture lignolytic and cellulolytic) formulated with edamame waste on feed intake, growth, and feed efficiency of sheep. Nine local sheep were assigned using completely randomized design, treated with 3 levels of exogenous enzyme i.e. 0, 1.4, and 2.8 g/kg of total mixed ration formulated using edamame waste. The sheep were reared in individual cage and given treatment in 3 replications. Feeding and drinking were ad libitum and after two weeks feed intake (FI), average daily gain (ADG) and feed conversion ratio (FCR) were calculated. FI was significantly affected by the treatment and FI significantly increased in line with the treatment levels. However exogenous enzyme did not affect ADG and FCR